Application of medical cannabis in unstable angina and coronary artery disease: A case report. Issue 11 (19th March 2021) - Shaffer, Brian L.; Davis, Garrison M.; Incitti, Marc A.; Piper, Brian J.; Entler, Brian V.
Abstract: Rationale: First discovered in 1990, the endocannabinoid system (ECS) was initially shown to have an intimate relationship with central areas of the nervous system associated with pain, reward, and motivation. Recently, however, the ECS has been extensively implicated in the cardiovascular system with contractility, heart rate, blood pressure, and vasodilation. Emerging data demonstrate modulation of the ECS plays an essential role in cardio metabolic risk, atherosclerosis, and can even limit damage to cardiomyocytes during ischemic events. Patient Concerns: This case describes a 63-year-old man who presented to a primary care physician for a medical cannabis (MC) consult due to unstable angina (UA) not relieved by morphine or cardiac medications; having failed all first- and second-line polypharmaceutical therapies. The patient reported frequent, unprovoked, angina and exertional dyspnea. Diagnosis: Having a complex cardiac history, the patient first presented 22 years ago after a suspected myocardial infarction. He re-presented in 2010 and underwent stent placement at that time for inoperable triple-vessel coronary artery disease (CAD) which was identified via percutaneous transluminal coronary angioplasty. UA developed on follow-up and, despite medical management over the past 6 years, became progressively debilitating. Interventions and Outcomes: In conjunction with his standard cardiac care, patient had a gradual lessening of UA-related pain, including frequency and character, after using an edible form of MC (1:1 cannabidiol:Δ 9 -tetrahydrocannabinol). Following continued treatment, he ceased long-term morphine treatment and described the pain as no longer crippling. As demonstrated by his exercise tolerance tests, the patient experienced an improved functional capacity and reported an increase in his daily functioning, and overall activity. Lessons: This case uniquely highlights MC in possibly reducing the character, quality, and frequency of UA, whereas concordantly improving functional cardiac capacity in a patient with CAD. Additional case reports are necessary to verify this. Abstract : Supplemental Digital Content is available in the text